EFFECT OF RECEIVE BANDWIDTH’S VARIATION TO SIGNAL TO NOISE RATIO (SNR) AND CONTRAST TO NOISE RATIO (CNR) ON MRI EXAMINATION OF CERVICAL WITH T2 WEIGHTED FAST SPIN ECHO SEQUENC HERNIA NUCKLEUS PULPOSUS (HNP) CASE - Muhammad Raizal Rais; Bagus Abimanyu; Darmini Darmini (Jurnal Imejing Diagnostik (JImeD), 2018)
Background : The received bandwidth parameter is a parameter that can affect the value of SNR and CNR. The use of bandwidth value on the MRI 1.5 Tesla for cervical MRI examination with T2 Weighted Fast Spin Echo sequence axial used a value of 27.87Hz/px. By doing the variation of bandwidth, the quality of SNR and CNR image is different. The purpose of this study is to determine the effect of bandwidth variation on SNR and CNR. To know the optimal value of receive bandwidth variation on cervical MRI examination with T2 Weighted Fast Spin Echo sequence in Herniated Nuckleus Pulposus (HNP) case.Methods : This type of research is qualitative research with experimental approach. This study was conducted using MRI GE 1.5 Tesla at Bethesda Hospital Yogyakarta. Data in the form of 10 images of cervical MRI T2 FSE axial slice of 10 patients with 3 received bandwidth variation (20.83Hz / px, 27.87Hz / px and 31.25Hz / px). To determine SNR and CNR values, Region of Interest (ROI) with size 1mm2 were placed on Discus Intervertebralis, Cerebrospinal Fluid, Spinal Cord and Ligament Flavum. And to get the average value of the signal then the averageof signal was divided by the standard deviation from the background. The analysis was done by linear regression test and friedman mean rank test.Results : The result of research shows that there is influence between receive bandwidth variation on SNR and CNR cervical. The value of 20,83Hz/px receive bandwidth variation in cervical MRI examination with T2 Weighted Fast Spin Echo sequence result in optimal SNR and CNR value.Conclusion : There was the effect of the receive bandwidth of the SNR and CNR on MRI cervical sequences T2WI FSE axial. Receive Bandwidth optimum value in MRI cervical T2WI FSE axial is 20,83Hz/px.